Impact of Passive Filter Capacitor Failure on Harmonic Propagation in VSD-Driven ESP Systems - Benriwati Maharmi; Apriadi Apriadi; Fitri Ayu (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2026)
Passive LC filters are commonly installed at the output of Variable Speed Drives (VSDs) to limit harmonic distortion in Electrical Submersible Pump (ESP) systems. However, capacitor degradation may reduce filter effectiveness and alter the electrical behavior of the entire drive system. This paper examines the impact of passive filter capacitor failure in a 390 kVA VSD-driven ESP installation using field measurements obtained under three operating conditions: before the filter, during normal LC filter operation, and after disconnection of a failed 200 ?F capacitor while the output reactor remained in service. Harmonic performance was evaluated in accordance with IEEE Std 519-2022, followed by impedance and resonance analyses to explain the measured responses. The results indicate that capacitor removal increased THDi from 4.30% to 12.30% and THDv from 39.50% to 61.23%, confirming a substantial reduction in harmonic suppression capability. The analytical evaluation further shows that changes in filter impedance promote resonance between the output reactor and the downhole cable capacitance. A preliminary single-tuned passive filter design is finally proposed to improve harmonic mitigation under comparable operating conditions.